Fast Pyrolysis of Municipal Green Waste in an Auger Reactor: Effects of Residence Time and Particle Size on the Yield and Characteristics of Produced Oil - Hasan, MM; Rasul, MG; Jahirul, MI; Khan, MMK (MDPI AG, 2024)
The development of renewable sources for energy production has assumed a vital role in recent years, particularly with regard to the preservation of energy supplies and the environment. In this regard, municipal green waste (MGW) can be a potential renewable energy source if it is integrated with emerging technology, like pyrolysis. Therefore, this study aimed at investigating the effect of residence time and particle size on the yield and composition of oil derived from MGW using fast pyrolysis in an auger reactor. The residence time and particle size were varied from 1 min to 4 min and 1 mm to 10 mm, respectively, while keeping the temperature constant at 500 °C. At a residence time of 3 min, a 2 mm particle size provided the highest bio-oil yield (39.86%). At this experimental setting, biochar yield of 27.16% and syngas yield of 32.98% were obtained. The characterization of produced bio-oil revealed that a total of nine functional groups were present in the bio-oil. The phenols were highest in amount, followed by aromatics and ketones. The increase in residence time decreased the amount of acidic compounds present in the bio-oil. The water content was decreased by ~11% and the calorific value was increased by ~6% with the increase in particle size from 1 mm to 10 mm. Other properties, such as viscosity, density, cetane number, and flash point, did not change significantly with the change in experimental conditions. With a calorific value of 25+ MJ/kg, although the bio-oil produced from MGW can be used for heating (such as in boilers and furnaces), the use of MGW bio-oil in engines requires appropriate upgrading through procedures like hydrodeoxygenation, catalytic cracking, esterification, etc.
Keywords: 40 Engineering; 33 Built Environment and Design; 51 Physical Sciences; 7 Affordable and Clean Energy; 13 Climate Action; 02 Physical Sciences; 09 Engineering; 33 Built environment and design; 40 Engineering; 51 Physical sciences